Qualifizierung einer Prozesskette zum Laserstrahlsintern metallischer Bauteile - Niebling, Frank (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2005)
lnvestigation of the temperature- and stress field at laser sintering of metal parts. A two step process - laser sintering at low area energies followed by an infiltration - is usually faster and more economical than the conventional laser sintering process. Additionally the process stability at laser sintering was improved by an optimisation of the process parameter